Future of legal training. Special approach to the public examinations system - Calvo González-Vallinas, Dulce (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
After a brief assessment of the evolution of the Spanish educational system, this article tries to analyze how the academic training of the jurist in the mid-21st century could be adapted to meet the demands of modern society. Likewise, an approximation is made to the public examination system for access to the public service, which is positively evaluated, notwithstanding the possibility of its improvement and adaptation.